Accuracy of Urine Calprotectin in the Diagnosis of Acute Kidney Injury in Neonates: A Cross-Sectional Study - Nasrin Khalesi; Shima Mohammadian; Nakysa Hooman; Mahmoud Khodadost; Leila Allahqoli (Mashhad University of Medical Sciences, 2021)
Background: Urine calprotectin significantly elevates in acute kidney injury (AKI) in adult and pediatric patients. The present study aimed to assess the accuracy of urine calprotectin as a diagnostic marker for (AKI) in neonates.Methods: This cross-sectional study assessed urine calprotectin in 100 neonates (80 newborns with confirmed AKI and 20 healthy ones). Random urine calprotectin was measured by Enzyme-linked Immunosorbent Assay (ELISA) and then compared between the two groups. We included the neonates who had received at least 48 h of intravenous fluid and met the inclusion and exclusion criteria. Receiver-operating characteristic (ROC) curve was used to set a cut-off point for urine calprotectin for the prediction of AKI. The overall accuracy and Kappa coefficient were used to assess the agreement between the two methods. A p-value less than 0.05 was considered statistically significant. Results: Urine calprotectin levels were not significantly higher in neonates with AKI, as compared to those in the healthy ones (146.2 versus 142.4; P=0.1). The results pointed to an optimal cut-off value of 123.5 mg/dl for urine calprotectin with the area under the curve of 0.515 (the sensitivity, specificity, positive predictive value, and negative predictive value were obtained at 77.5%, 40%, 83.7%, and 30.7%, respectively). The overall accuracy and Kappa agreement coefficient were reported as 70% and 0.15, r (P=0.11). Conclusion: As evidenced by the results of the resent study, although urine calprotectin level elevates in AKI in neonates, it is not more sensitive than gold standards to predict AKI.